Recent Advances Targeting CCR5 for Cancer and Its Role in Immuno-Oncology - Xuanmao Jiao; Omar Nawab; Tejal Patel; Andrew V. Kossenkov; Niels Halama; Dirk Jaeger; Richard G. Pestell (2019)
Abstract Experiments of nature have revealed the peculiar importance of the G-protein–coupled receptor, C-C chemokine receptor type 5 (CCR5), in human disease since ancient times. The resurgence of interest in heterotypic signals in the onset and progression of tumorigenesis has led to the current focus on CCR5 as an exciting new therapeutic target for metastatic cancer with clinical trials now targeting breast and colon cancer. The eutopic expression of CCR5 activates calcium signaling and thereby augments regulatory T cell (Treg) differentiation and migration to sites of inflammation. The misexpression of CCR5 in epithelial cells, induced upon oncogenic transformation, hijacks this migratory phenotype. CCR5 reexpression augments resistance to DNA-damaging agents and is sufficient to induce cancer metastasis and “stemness”. Recent studies suggest important cross-talk between CCR5 signaling and immune checkpoint function. Because CCR5 on Tregs serves as the coreceptor for human immunodeficiency virus (HIV) entry, CCR5-targeted therapeutics used in HIV, [small molecules (maraviroc and vicriviroc) and a humanized mAb (leronlimab)], are now being repositioned in clinical trials as cancer therapeutics. As CCR5 is expressed on a broad array of tumors, the opportunity for therapeutic repositioning and the rationale for combination therapy approaches are reviewed herein.